(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines adaptive sports as a powerful tool for socialization and rehabilitation of veterans with physical injuries, contributing to their physical, psychological and social development. By engaging in sports activities, veterans are able to feel the support of like-minded people, expand their social contacts and restore their sense of self-worth. The aim of the article is to analyze the role of adaptive sports in the socialization of veterans with physical injuries. Studies confirm that participation in adaptive sports has a positive impact on the quality of life of veterans, reducing the level of isolation and promoting integration into society. In addition, sports can improve well-being, increase self-esteem and find new opportunities for professional and personal development. Using the example of international competitions such as the Invictus Games, we observe that adaptive sports not only help veterans recover physically, but also contribute to their motivation to achieve new goals and self-realization. An important task is the further development and popularization of adaptive sports, the creation of new rehabilitation programs and accessible opportunities for veterans to participate in sports events. The involvement of state and public organizations, as well as international experience, will contribute to improving the situation and expanding opportunities for veterans with physical injuries. Adaptive sports play a key role in the physical and psychological rehabilitation of Ukrainian veterans, helping them return to active life and integrate into society. Despite the challenges, the development of this area in Ukraine has significant potential and requires further support from the state, the public and international partners. Supporting veterans through sports is not only a matter of health, but also an important step towards their social adaptation and a dignified life.